The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ecs2.3696
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term monitoring using DNA sampling reveals the dire demographic status of the critically endangered Gobi bear

Abstract: Long-term monitoring using DNA sampling reveals the dire demographic status of the critically endangered Gobi bear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Geographic isolation, possibly exacerbated by anthropogenic influences and adaptations to the different environmental conditions in the Gobi and Himalayas, may have played an important role in separating these lineages. The combination of restricted gene flow and small population sizes (Tumendemberel et al, 2021) likely increased genetic drift leading to low genetic diversity and further genetic differentiation. Previous research using microsatellites demonstrated that Gobi bears were the most divergent of all groups sampled in Central Asia (Tumendemberel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geographic isolation, possibly exacerbated by anthropogenic influences and adaptations to the different environmental conditions in the Gobi and Himalayas, may have played an important role in separating these lineages. The combination of restricted gene flow and small population sizes (Tumendemberel et al, 2021) likely increased genetic drift leading to low genetic diversity and further genetic differentiation. Previous research using microsatellites demonstrated that Gobi bears were the most divergent of all groups sampled in Central Asia (Tumendemberel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated population structure using the LEA R package (Frichot & François, 2015) admixture analysis based on sparse nonnegative matrix factorization (snmf; Frichot et al, 2014) with 50 repeats for the full dataset and 10 repeats for the brown bears only dataset and principal component analysis (PCA) using Plink v1.90 (Chang et al, 2015). Results were visualized using the ggplot2 package (Wickham, 2016) in program R v.4.0 (Team R. C., 2017). We used spectacled bear as an outgroup to conduct phylogenetic analysis.…”
Section: Population Structure and Phylogenymentioning
confidence: 99%